The Influence of Student Experiences, Institution Image, and Perceived Quality on Students' Satisfaction At Al-Amjad Islamic Education, Medan - Achmad Afriadi Trisatya; Syafrizal Helmi Situmorang; Endang Sulistya Rini (Program Pascasarjana Universitas Negeri Makassar, 2023)
The purpose of this research is to examine various variables of student experience, institutional image, perceived quality on student satisfaction. This research was conducted in December 2022 with 100 students at the Al-Amjad School as respondents. This study uses a quantitative descriptive approach with random sampling. This study uses data analysis, namely the validity and reliability of using the model structure (PLS-SEM) with smartpls used to test the model using path analysis. Based on the results of the study, it shows that student experience has no effect on student satisfaction. The results of the study also found that student experience proved to have an effect on institutional image. Then, institutional image and perceived value are proven to have a positive and significant effect on student satisfaction.